The Charangas of Bejucal, emergence, evolution and perception from the preservation of the patrimony that you/they represent - Fernández García, Renier Helvio (2024)
He is carried out an evolutionary historical analysis of the Charangas of Bejucal, recognizing from their emergence the importance to the traditional culture of the nation; transcending until our days their legacy. He/she is also necessary the investigator's perception regarding their current state and the necessity of rescuing traditions a so much forgotten, contributing to the preservation and patrimonial administration, leaving white their necessity and historical transcendency - cultural concrete, not alone for the territory, but for the nation and the universal cultural patrimony.